2018
DOI: 10.1155/2018/2549451
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Lethal Gaucher Disease due to RecNcil Recombinant Mutation in the GBA Gene Presenting with Hydrops Fetalis and Severe Congenital Anemia

Abstract: A 35-year-old woman presented at 27-week gestation with hypertension and pedal edema. Antenatal scan showed hydrops fetalis and growth restriction. Cordocentesis showed severe fetal anemia. This was treated with multiple in utero blood transfusions with no clinically significant improvement and intrauterine death occurred at 28 weeks. Perinatal autopsy confirmed severe hydrops with hepatosplenomegaly and visceral effusions. Microscopic examination of the reticuloendothelial organs showed widespread infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Unfortunately, there is no definitive treatment available now for perinatal lethal complications when fetal ascites, hydrops, and/or hepatomegaly are prenatally diagnosed. Only symptomatic management can be considered, i.e., in fetal anemia (suspected based on middle cerebral artery peak systolic velocity, MCA-PSV and placentomegaly), transfusions are an option [ 15 ]; occasionally, in case of poly- or oligohydramnios (mentioned in Table 1 ) only symptomatic treatment is available. Otherwise, the pregnancy needs to be monitored, and optimal delivery time has to be planed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is no definitive treatment available now for perinatal lethal complications when fetal ascites, hydrops, and/or hepatomegaly are prenatally diagnosed. Only symptomatic management can be considered, i.e., in fetal anemia (suspected based on middle cerebral artery peak systolic velocity, MCA-PSV and placentomegaly), transfusions are an option [ 15 ]; occasionally, in case of poly- or oligohydramnios (mentioned in Table 1 ) only symptomatic treatment is available. Otherwise, the pregnancy needs to be monitored, and optimal delivery time has to be planed.…”
Section: Discussionmentioning
confidence: 99%
“…As presented in Table 1 , the severe GD form usually manifests in the neonatal period with small birth weight, massive hepatosplenomegaly and ascites. In many cases, akinesia or joints contractures were described [ 8 , 13 , 15 , 16 ]. Decreased spontaneous movements at birth, followed by hypertonia and progressive neurologic deterioration, can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Bhutada, Pyragius, Petersen, Niemann, and Matsika (2018) reported a case of Perinatal-lethal GD prenatally presenting thrombocytopenia, transfusion refractory severe anemia, and non-immune fetal hydrops. In this case report, the genetic analysis revealed that the fetus was homozygous for the RecNciI variant in the GBA1 which usually causes severe phenotypes (Bhutada et al, 2018). This variant occurs due to recombination events between GBA1 and its highly homologous pseudogene located 16 kb downstream, known as GBAP (Tayebi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…While GD type II is generally associated with specific mutations in GBA1, there is also significant genotypic heterogeneity and genotype-phenotype associations are not conclusive (Eblan, Goker-Alpan, & Sidransky, 2005). Bhutada, Pyragius, Petersen, Niemann, and Matsika (2018) reported a case of Perinatal-lethal GD prenatally presenting thrombocytopenia, transfusion refractory severe anemia, and non-immune fetal hydrops. In this case report, the genetic analysis revealed that the fetus was homozygous for the RecNciI variant in the GBA1 which usually causes severe phenotypes (Bhutada et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The sister's second (VI3) fetus was noted to have anemia and thrombocytopenia on evaluation. The fetal autopsy and NIHF/ LSD gene panel testing were done in that case by Bhutada et al [4] With the above family history in mind, the couple was counselled that although their baby's presentation was different, there was a high suspicion of the same genetic condition as that identified in the sister's fetus. A prenatal diagnosis by amniocentesis and targeted molecular testing for the identified recombinant GBA variant was done which confirmed the fetus to be homozygous for the same.…”
Section: Case Reportmentioning
confidence: 99%